Resin-assisted solvothermal synthesis of metal-organic frameworks. - Du, Y; Thompson, A; O'Hare, D (2008)
Transition metal-exchanged polymer resin beads have been used as a heterogeneous controlled-release source of metal cations in high yielding, phase pure solvothermal syntheses of novel transition metal-organic frameworks.